Detection of immune-mediated tumour cell death in vivo using Zirconium-89-labeled APOMAB® - Vasilios Liapis; Nicole L. Wittwer; William Tieu; Tessa Gargett; Michael P. Brown; Alexander H. Staudacher (Journal of Translational Medicine)
Abstract Background Inconsistent responses to anticancer immunotherapies demonstrate the need for non-invasive methods to detect treatment responses earlier than conventional medical imaging methods allow. The chimeric monoclonal antibody, APOMAB®, targets dead tumour cells following DNA-damaging anticancer treatments via binding of the ribonuclear protein, La/SSB, an intracellular protein overexpressed by tumour cells. La/SSB only becomes accessible to APOMAB binding in post-apoptotic necrotic tumour cells. Methods We assessed the ability of APOMAB to detect dead tumour cells after immune-mediated cell death. Co-culture of GD2-specific chimeric antigen receptor (CAR) T-cells with GD2-expressing cancer cell lines demonstrated specific and dose-dependent binding of APOMAB to the resulting dead target cells, confirming detection of immune-mediated cell death. Then, using four distinct preclinical tumour models and in a cancer patient, we investigated APOMAB-immunoPET as a technique to detect immune-mediated tumour cell death. Results Within days of treatment, APOMAB-immunoPET showed increased tumour uptake of 89Zirconium-labelled APOMAB (89Zr-APOMAB) after CAR-T cell therapy, immune checkpoint inhibitor (ICI) therapy with and without chemotherapy, and via endogenous T-cell mediated tumour clearance. In a metastatic melanoma patient after ICI therapy, a previously FDG-avid pulmonary tumour reduced in size as tumour 89Zr-APOMAB uptake increased over the 12-day scanning period. Conclusions This study demonstrates for the first time that not only does radiolabelled APOMAB provide an initial direct measure of the extent of immune-mediated tumour cell death in vivo but also reveals the heterogeneous nature of tumour responses to T-cell based therapies both within and between individuals.